Investigation of gas permeation properties of systematically modified polybenzimidazoles by N-substitution - Kumbharkar, Santosh C.; Kharul, Ulhas K. (Journal of Membrane Science, 2010)
Gas permeation behavior of a series of thermally stable N-substituted polybenzimidazoles by systematically varying bulk and flexibility of the substituent was investigated. Two different PBIs having variation in their acid moiety, viz., PBI-I (based on isophthalic acid) and PBI-BuI (based on 5-tert-butyl isophthalic acid) were selected for N-substitution by alkyl groups possessing different bulk and flexibility. These substituent groups were methyl, n-butyl, methylene trimethylsilane and 4-tert-butylbenzyl. Pure gas sorption and permeability using H(2), N(2), O(2), CH(4) and CO(2) were investigated and correlated with physical properties of formed polymers. Estimation of dual-mode sorption parameters, coefficients of sorption, permeability and diffusion for different gases provided an insight towards effects of nature of a substituent group and parent PBI on governing gas sorption and permeation properties. By changing the substituent group, diffusivity coefficients was found to vary to a larger extent than the solubility coefficient. This significantly enhanced gas permeability for different gases by 1.2-129 times than that of parent PBIs. The permselectivity P(O2)/P(N2) was increased (up to 237%), while for other gas pairs, it was decreased to a different extent. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Diffusion; Gas permeation; N-Substitution; Polybenzimidazole; Sorption